Simulating Two-Phase Viscoelastic Flows Using Moving Finite Element Methods (Communications in Computational Physics, 2018)
Phase-field models provide a way to model fluid interfaces as having finitethickness; the interface between two immiscible fluids is treated as a thin mixing layeracross which physical properties vary steeply but continuously. One of the main challengesof this approach is in resolving the sharp gradients at the interface. In this paper,moving finite-element methods are used to simulate interfacial dynamics of two-phaseviscoelastic flows. The finite-element scheme can easily accommodates complex flowgeometry and the moving mesh strategy can cluster more grid points near the thin interfacialareas where the solutions have large gradients. A diffused monitor function isused to ensure high quality meshes near the interface. Several numerical experimentsare carried out to demonstrate the effectiveness of the moving mesh strategy.